2017
DOI: 10.1021/acschemneuro.6b00349
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition and Degradation of Amyloid Beta (Aβ40) Fibrillation by Designed Small Peptide: A Combined Spectroscopy, Microscopy, and Cell Toxicity Study

Abstract: A designed nontoxic, nonhemolytic 11-residue peptide, NF11 (NAVRWSLMRPF), not only inhibits the aggregation of amyloid beta (Aβ40) protein but also disaggregates the preformed oligomers and mature Aβ fibrils, thereby reducing associated-toxicity. NMR experiments provide evidence of NF11's ability to inhibit fibril formation, primarily through interaction with the N-terminus region as well as the central hydrophobic cluster of Aβ40. NF11 has micromolar binding affinity toward both monomeric and aggregated speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 29 publications
0
29
0
Order By: Relevance
“…To this aim, several natural antioxidants as silymarin, bacoside-A, and resveratrol have evidenced antioxidant effects and are currently under clinical investigation [24,25,26,27]. Among natural antioxidants, Panax ginseng C.A.…”
Section: Introductionmentioning
confidence: 99%
“…To this aim, several natural antioxidants as silymarin, bacoside-A, and resveratrol have evidenced antioxidant effects and are currently under clinical investigation [24,25,26,27]. Among natural antioxidants, Panax ginseng C.A.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study by Ghosh et al . showed the ability of an 11-mer peptide (NF11) to interact with the N-terminus region as well as the central hydrophobic cluster of Aβ40 to stop fibrillization and diminish existing mature fibrils 25 . Clearly, there is an interest to find potent molecules with “dual functionalities” i.e.…”
Section: Introductionmentioning
confidence: 99%
“…59 Similarly, prostatespecific antigen and matriptase, which are proteases in seminal plasma degraded SEVI amyloid fibrils. 60 A recent study showed disaggregation of Ab(1-40) amyloid fibrils by nonhemolytic 11-residue peptide (NAVRWSLMRPF), 61 which suggested the possible application of this short peptide for eliminating SEVI amyloid fibrils and peptidomimetic therapeutic agents against amyloid disease.…”
Section: Reverse and Dissociate Sevi Amyloid Fibrils (Methods 3)mentioning
confidence: 99%
“…78 In addition, nonhemolytic 11-residue peptides inhibited the formation of Ab(1-40) amyloid fibrils by interacting with the N-terminal part and the central hydrophobic cluster of Ab . 61…”
Section: Stabilization Of Sevi Precursors (Methods 7)mentioning
confidence: 99%
See 1 more Smart Citation